Analysis of Implementation of Carbon Tax Policy in Efforts to Address Climate Change Issues with Studies in Australia, Japan, Colombia, and Indonesia - Putri, Hannisa Oktora; Hutapea, Riauli Susilawaty (Jurusan Akuntansi Politeknik Negeri Bandung, 2024)
The Indonesian government's commitment to reducing carbon emissions in order to handle climate change, one of which is the carbon pricing policy implemented through the carbon tax instrument. However, in practice, the implementation of the carbon tax has been delayed until 2025. This research is done to know about how carbon tax rate, and the implementation of carbon tax policies in Australia, Japan, and Colombia is then compared to the planned implementation in Indonesia based on Law Number 7 of 2021. The research method used is comparative qualitative, with data collection methods in the form of documentation and literature study. There are several things that deserve review in the implementation of this carbon tax policy, including those related to governance, regulatory arrangements, and economic and social preparedness.